Accuracy of the diagnosis of gastroesophageal reflux disease by a trial of potassium-competitive acid blocker treatment - Peiwen Dong; Lin Lin; Kaidi Sun; Feng Tang; Qian Li; Xinxu Zhou; Fuli Liu; Zhilin Yang; Jiao Li; Lin Jiang; Ping Zhao; Xiaobin Sun; et al. (BMC Gastroenterology)
Abstract Aim The aim of this study was to explore the accuracy of the diagnosis of gastro-esophageal reflux disease (GERD) through tegoprazan treatment trials, and to analyze factors that may influence test accuracy. Methods This was a single-blind, single-arm 2 weeks tegoprazan treatment trials from March 2023 to April 2024. Patients with ‘typical’ reflux or heartburn as their most troublesome symptom who were considered likely to have GERD were recruited.: Patients were submitted to endoscopy and/or esophageal pH monitoring. After the recording patient used tegoprazan for 2 weeks. This was defined as positive for tegoprazan therapy if the scores for symptoms have decreased to 50%, 75% and 100% of the baseline after 1 and 2 weeks. Calculate different sensitivity, specificity and Youden index for each criterion. Results This represents a mid-term report from the study, with 98 and 91 fully evaluable at one and two weeks. The Youden index indicated that a symptom relief of > 75% after one week offers greater diagnostic value with sensitivity and specificity of 77.5% and 51.9%. Multivariate regression analysis indicated that lower BMI, preference for coffee, endoscopic mucosal erosion, ineffective esophageal peristalsis and positive SAP are independent risk factors predicting the efficacy of P-CAB treatment. Conclusions The P-CAB test (tegoprazan) presents a promising tool for the diagnosis of GERD. A one-week treatment with a criterion of 75% reduction in symptom scores from baseline may be the most cost-effective approach. Trial registration chictr.org.cn registration number ChiCTR2200065994.